Efficacy and Safety of Trastuzumab Biosimilar (CT-P6) Compared With Reference Trastuzumab in Patients With HER2-positive Advanced Gastric Cancer: A Retrospective Analysis. (February 2022) - Park, Joo-Hwan; Yeo, Ja Hyun; Kim, Young Saing; Park, Inkeun; Ahn, Hee Kyung; Cho, Eun Kyung; Shin, Dong Bok; Yang, Jun-Young; Kim, Hyung-Sik; Lee, Woon Kee; Sym, Sun Jin
Abstract : Objectives: Treatment with trastuzumab and chemotherapy significantly improves the outcome in patients with human epidermal growth factor receptor 2 (HER2)-positive advanced gastric cancer (AGC). CT-P6 (trastuzumab-pkrb; Herzuma) is a trastuzumab biosimilar approved for the treatment of HER2-positive gastric cancer. In this study, we aimed to compare the efficacy and safety of CT-P6 and reference trastuzumab as first-line treatment for HER2-positive AGC. Materials and Methods: The medical records of 102 patients with HER2-positive AGC treated with first-line trastuzumab-based chemotherapy were retrospectively reviewed. These patients were treated with either reference trastuzumab (n=72) or a biosimilar (n=30). Treatment outcomes, such as objective response rate, progression-free survival (PFS), and overall survival (OS), were compared between the reference and biosimilar groups. Results: The objective response rate of both groups (52.8% and 56.8% in the reference and biosimilar groups, respectively) were comparable ( P =0.72). No statistically significant difference was observed with the reference versus biosimilar trastuzumab for PFS (median PFS, 6.9 vs. 5.4 mo; P =0.98) or OS (median OS, 12.3 mo vs. not reached; P =0.42). Safety profiles were similar between the 2 groups. Conclusions: Biosimilar trastuzumab showed equivalent outcome to reference trastuzumab, with similar adverse events. Biosimilar trastuzumab can suitably and safely replace trastuzumab as a reference for the treatment of HER2-positive AGC.